Trust as Mediator of Online Reviews, Price Perception, Website Quality, and Purchase Decisions - Muhammad Iqbal Ismail; Maya Sova; Forbis Ahamed (Journal of Business and Economics Research (JBE), 2026)
This study examines the influence of online reviews, price perception, and website quality on purchase decisions, with trust as a mediating variable among Generation Z Shopee users in Indonesia. This research adopts a quantitative approach using survey data collected from 250 respondents and analyzed using Partial Least Squares Structural Equation Modeling. The findings show that website quality has the strongest direct effect on purchase decisions (β = 0.275; p < 0.001), followed by price perception (β = 0.227; p = 0.006) and online reviews (β = 0.225; p = 0.012). Trust also has a significant effect on purchase decisions (β = 0.191; p = 0.002). Furthermore, trust significantly mediates the effects of online reviews (β = 0.050; p = 0.045), price perception (β = 0.051; p = 0.048), and website quality (β = 0.050; p = 0.014) on purchase decisions. The model explains 57.6% of the variance in purchase decisions and 45.4% of the variance in trust. These findings indicate that purchase decisions among Generation Z Shopee users are shaped by informational, economic, technological, and psychological factors. This study contributes to digital marketing and consumer behavior literature by providing empirical evidence on the mediating role of trust in e-commerce decision-making. Practically, the results suggest that e-commerce platforms should improve website quality, pricing strategies, and review credibility to strengthen consumer trust and purchasing behavior.